Molecular and Immunological Characterization of Staphylococcus aureus in Pediatric Atopic Dermatitis: Implications for Prophylaxis and Clinical Management - Chiara Pascolini; JoLinda Sinagra; Simone Pecetta; Valentina Bordignon; Alessandra De Santis; Laura Cilli; Viviana Cafiso; Grazia Prignano; Bruno Capitanio; Claudio Passariello; Stefania Stefani; Paola Cordiali-Fei; et al. (Clinical and Developmental Immunology)
S. aureus represents a critical cofactor in atopic dermatitis (AD). In this paper, the prevalence of S. aureus infection/colonization was evaluated in 117 children as well as in their cohabitants, in order to assess the value of S. aureus characterization in predicting disease onset and severity and in providing indications for prophylaxis. Results showed that children with AD as well as their cohabitants had a significantly greater incidence of S. aureus infection/colonization as compared to controls. The genetic characterization showed a virtual identity of the bacteria strains collected at different sites of the patients with those found in the cohabitants, suggesting both a direct transmission between the nasal reservoir and the lesions in the same atopic subject and a risk for reinfection within family cohabitants. These data stress the need of preliminary laboratory assessment and posttherapy control in both AD patients and their close contacts for effective S. aureus eradication.